Partisipasi Masyarakat dalam Pengembangan Objek Wisata Srambang Park (Studi Kasus Wisata Srambang Park) - Nimastuti, Erysa; Wibowo, Agung; Lestari, Eny (Department of Agribusiness, Halu Oleo University, 2021)
Tourism object is one of the important sectors for the country because it contributes quite a lot of foreign exchange. Tourism objects require management in periodic and sustainable development. The development of regional things cannot be separated from the participation of the community and the government. This study aims to analyze community participation in the development of Srambang Park tourism objects, including community participation in the participation stages, supporting and inhibiting factors of development, motivation to participate, and developing the impact of tourism objects on economic, social environmental aspects. The research method used in this research is descriptive qualitative. The research was conducted on 20-25 May 2021 with seven informants. The research location is in Srambang Park, Girimulyo Village, Paron District, Ngawi Regency. The results of the study indicate that community participation is very active in the development of tourism objects. This activity can be reflected in the community's involvement in the tourist attraction by becoming a motorcycle taxi driver, parking attendant, trader, and employee. Supporting factors include tourist attraction, marketing, infrastructure, and stakeholders. The inhibiting factor for the development of tourism objects is the existence of a pandemic that occurred in early 2020. The motivation of the community to participate in the development of tourism objects is because of the opportunities, desires, and needs. The impact arising from the existence of a tourist attraction is an average positive economic, social and environmental impact.